Brinch Hansen on Pascal compilers - Brinch Hansen, Per (London, United Kingdom : Prentice-Hall International Ltd., 1985)
The book does not attempt to cover different compilation methods. Such an attempt is often confusing for the beginner, who may have difficulty seeing how all the parts of a compiler fit together.
1. What a compiler does -- 2. A pascal subset -- 3. Compiler organization -- 4. Lexical analysis -- 5. Syntax analysis -- 6. Scope analysis -- 7. Type analysis -- 8. A pascal computer -- 9. Code generator -- 10. Performance.
Includes bibliographical references and index.
Keywords: PASCAL (COMPUTER PROGRAM LANGUAGE)